KEBERADAAN KAPANG PENGKONTAMINASI KEMIRI (Aleurites moluccana Willd.) YANG DIJUAL DI PASAR RAYA PADANG - Misdar, Zelvia; Fifendy, Mades; Nurmiati, Nurmiati (Pendidikan Biologi, 2013)
ABSTRACTHazelnut is the spice material include dried spices sold in seed fotm. Many hazelnut used commoncy in cook eat like that, curry goat, rendang, asam padeh and etc by people. Hazelnut had solded in the Market in the open area and dont use of packaging. The condition like that hazelnut is dray will be easy damp, because it deals directly with the muggy air. It is will make the microorganism easily grow. This study for know the types of moulds contaminating Hazelnut (Aleurites moluccana Willd.) sold in Market. The study used survey method in the field with the simple random sampling technic. Descriptive observation of the isolated moulds that grow on the media, make oblique and identify to species lievel. Result of isolation and identification of a sample Hazelnut (Aleurites moluccana Willd.) found five types of kapang. It is find commoncy contaminants in foods like that, Aspergillus niger, Aspergillus sp.1 suspected Aspergillus flavus, Aspergillus sp.2 suspected Aspergillus oryzae, Penicillium sp. and Rhizopus oryzae. In conclusion hazelnut orkeon in that sold in the Market contaminated by moulds contaminations.